2014
DOI: 10.1161/circinterventions.114.001856
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Paraganglioma

Abstract: Paragangliomas are extraadrenal tumors that arise from chromaffin cells of the sympathetic ganglia. Cardiac paraganglia are exceptionally rare and because of paucity of cohort data, raises dilemmas about management when encountered. Some of them are metabolically active and may present with symptoms of catecholamine excess, whereas some may be incidentally diagnosed. In this report, we discuss the challenges surrounding the diagnosis and management of a cardiac paraganglioma at each stage. Case PresentationA 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…An additional 2.5% mortality was reported for the immediate postoperative course. A review of individual case reports from 2014-2016, two years since Wang et al's review, shows no intraoperative mortality reported from 11 cases (12,18,19,(22)(23)(24)(25)(26)(27). Among these cases, one instance of intraoperative cardiac arrest occurred due to severe hemorrhage and one unexpected intraoperative circulatory collapse, however both ended with successful outcomes (24,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional 2.5% mortality was reported for the immediate postoperative course. A review of individual case reports from 2014-2016, two years since Wang et al's review, shows no intraoperative mortality reported from 11 cases (12,18,19,(22)(23)(24)(25)(26)(27). Among these cases, one instance of intraoperative cardiac arrest occurred due to severe hemorrhage and one unexpected intraoperative circulatory collapse, however both ended with successful outcomes (24,26).…”
Section: Discussionmentioning
confidence: 99%
“…After recovery from surgery, benign cardiac PGs that are completely resected with negative margins have been associated with favorable outcomes in survival with low rates of tumor recurrence (18,26). For those surviving the immediate post-operative course, a 1-year survival of 98.2% and 5-year survival of 78.2% has been reported (17).…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Clinically, these can present without symptoms or with generalized complaints and signs of catecholamine excess. [ 4 ] The extreme variability in symptoms suggests a broad differential, which necessitates further investigation. There are many imaging options available, with no standard consensus on the most appropriate studies.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies have improved over the last few decades and have become very sensitive and specific for diagnosing and localizing cardiac PGs. Commonly used modalities include contrastenhanced computed tomography (CT) scan, dedicated cardiac magnetic resonance imaging (MRI), transthoracic echocardiogram (TTE), and coronary arteriography [23]. By echocardiography, cardiac PGs appear as large, echogenic masses [4].…”
Section: Diagnosismentioning
confidence: 99%
“…CT scan will show heterogeneous mass with peripheral enhancement and low attenuation areas due to tumor degeneration and necrosis [24]. By MRI, cardiac PGs are shown as well-circumscribed ovoid masses with hyperintense signals on the T2 imaging sequence [23]. Cardiac MRI is superior to CT scan and echocardiography for detection and evaluation of cardiac PGs [1].…”
Section: Diagnosismentioning
confidence: 99%